1972
DOI: 10.1104/pp.49.4.506
|View full text |Cite
|
Sign up to set email alerts
|

Short Term Metabolism of Urea and Purine Cytokinins

Abstract: Approximately 20 to 25% of the cytokinin benzyladenine (BA) taken up by soybean tissues in culture is converted to a stable, long-lived derivative which contains BA as part of its structure. This derivative may be metabolically related to 6-benzylamino 9-,B-D-ribofuranosylpurine 5'-monophosphate (BAMP). In in vivo incubations of 2 hours or less, we recover only BA, benzyladenosine, and BAMP. Benzyladenosine never accounts for more than 10% of the total radioactivity while BAMP builds up to about 20% of the tot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
33
0

Year Published

1972
1972
1989
1989

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(34 citation statements)
references
References 14 publications
1
33
0
Order By: Relevance
“…Recently, the short term metabolism of 6-benzylaminopurine (benzyladenine) in soybean tissue culture (6) or potato tuber slices (4) has been demonstrated. 6-Benzylaminopurine riboside and 6-benzylaminopurine ribotide were identified as products of the conversion of benzyladenine within 2 to 4 hr.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the short term metabolism of 6-benzylaminopurine (benzyladenine) in soybean tissue culture (6) or potato tuber slices (4) has been demonstrated. 6-Benzylaminopurine riboside and 6-benzylaminopurine ribotide were identified as products of the conversion of benzyladenine within 2 to 4 hr.…”
Section: Discussionmentioning
confidence: 99%
“…Adenine-8-'4C (8.4 mg, 1 mCi, 16.0 mCi/mmole), 8.4 mg (0.062 mmole) freshly prepared benzylamine hydrochloride, and 0.5 ml (46 mmole) of freshly distilled benzylamine were heated in a sealed ampoule at 175 C overnight. The contents of the ampoule were then transferred to a 15-ml centrifuge tube.…”
Section: Methodsmentioning
confidence: 99%
“…There (28), van Onckelen et al (32), and Fox et al (13,14) reported the incorporation of cytokinins into sRNA although the purity of some of the sRNA was later questioned by Key (19). Dyson (8) and Srivastava (31) into both tRNA and rRNA, whereas Hall (16), Richmond et al (26), and Bezemer-Sybrandy et al (3) failed to detect any incorporation into RNA. Kende and Tavares (18), on the basis of measurements of incorporation of radioactive 6-benzylaminopurine and 6-benzylamino-9-methylpurine into soybean callus, claim that the methyl substituent in the 9 position inhibited incorporation of the latter cytokinin into RNA without inhibiting its biological activity.…”
mentioning
confidence: 95%
See 1 more Smart Citation
“…In previous communications, it has been established that the cytokinin, 6-benzylaminopurine, is metabolized in relatively short time periods by cytokinin-requiring soybean tissues to yield three compounds containing the BA9 moiety in the soluble, nonpolynucleotide fraction (2,6). Two the these, 6-benzylamino-9-/8-D-ribofuranosylpurine and 6-benzylamino-9-fl-D-ribofuranosylpurine-5'-monophosphate, as well as BA itself, are relatively short lived and disappear within 120 hr, when the tissue is given an initial pulse of BA.…”
mentioning
confidence: 99%